Bibliometric analysis and visualisation of research on financial readiness - Nawi, H.M.; Ahmad, M. Y.; Yahaya, M. N.; Ariffin, Z. Z.; Abdullah, M. N.; Ismail, A.; Sabri, M. F. (Human Resource Management Academic Research Society, 2023)
Financial readiness has become a global concern that undermines individuals' financial security. This study focuses on examining the research progress on 'financial readiness', identifying the research significant areas, and recognizing the major players in the research. 222 documents were retrieved from the Scopus Core Collection database. Using VOSviewer 1.6.15 and Harzing Publish or Perish, respectively, this study created visuals and integrated data. Results indicated that research on financial readiness began as early as 1972. Early development was drawing the interest of only Western scholars, particularly those from the U.S. and the U.K. Between 2019 and 2020, the number of financial readiness-related research papers published continuously rose. The U.S. was the country undertaking the most research in this area, besides being home to the majority of schools researching the topic. It is anticipated that the findings will encourage future research and guide the progress of the field of study.